Role of T99mc-Sulesomab Immunoscintigraphy in the Management of Infection following Deep Brain Stimulation Surgery. (17th October 2011) - Real, Raquel; Linhares, Paulo; Fernandes, Hélder; Rosas, Maria José; Gago, Miguel F.; Pereira, Jorge; Vaz, Rui
Abstract : Infection constitutes a serious adverse event in patients submitted to deep brain stimulation, often leading to removal of the device. We set to evaluate the potential role of immunoscintigraphy withT 99m c -labelled antigranulocyte antibody fragments (T 99m c -sulesomab) in the management of infection following DBS.T 99m c -sulesomab immunoscintigraphy seems to correlate well with the presence and extent of infection, thus contributing to differentiate between patients who should remove the hardware entirely at presentation and those who could undergo a more conservative approach. Also, T 99m c -sulesomab immunoscintigraphy has a role in determining the most appropriate timing for reimplantation. Finally, we propose an algorithm for the management of infection following DBS surgery, based on the results of theT 99m c -sulesomab immunoscintigraphy.